Perception of phage therapy and research across selected professional and social groups in Poland - Żaczek, Maciej; Zieliński, Marcin W.; Górski, Andrzej; Weber-Dąbrowska, Beata; Międzybrodzki, Ryszard (Frontiers in Public Health, 2025)
There is no doubt that in the last 15 years phage therapy has re-emerged from the shadow of antibiotics, from the perspective of both scientists and various patient advocacy groups. Despite some important progress, there is little to no data on phage therapy perceptions in key groups, i.e., patients and their relatives, physicians and anyone who could potentially become infected with antibiotic-resistant bacteria. To the best of our knowledge, with 1,098 collected questionnaires, this article constitutes the first large-scale analysis on phage therapy perceptions, interest and knowledge among ordinary people in a country with a long, internationally recognized, tradition of treating patients with phages. In addition to 36 general questions addressed to everyone (including lay people), representatives of the health care sector and science and research sector received individually selected questions. Further, each participant had a chance to take part in a short quiz (consisting of 12 questions) verifying their basic knowledge about bacteriophages, their history, biology and therapeutic connotations. Awareness of antibiotic resistance was very high (above 90%) but contradicted the low level of knowledge about associated risks (12%). Consciousness of phage therapy varied between 8.9% (people taking care of household chores as their primary activity) to 37.7% (people with higher education) and 39.7% (inhabitants of large cities) while the readiness to use such treatments was very high (84.4%) despite the need to pay for it. The level of awareness of bacteriophages and phage therapy was clearly correlated with the acceptance of this type of treatment and the social acceptance to allocate further funds for the development of phage research. Interestingly, physicians were quite reluctant to deepen their knowledge in the field of phage therapy with just over one third (37.5%) ready to do so. With the COVID-19 pandemic in the background, we also explored how the pandemic influenced the interest in experimental therapies in general, which makes this article a potential universal compendium on perceptions of experimental therapies in the coming years.